Дослідження органолептичних показників якості емульсійних соусів з йодміщуючими добавками - Колісниченко, Тетяна Олександрівна; Прісс, Олеся Петрівна; Кюрчева, Людмила Миколаївна; Сефіханова, К. А.; Kolisnychenko, Tetiana; Priss, Olesia; Kiurcheva, Liudmyla; Sefikhanova, K. (Запоріжжя : 2023, 2023)
UA: У статті розглядаються основні етапи, напрямки і доцільність використання йодвміщуючих добавок вакаме та комбу у виробництві емульсійних соусів. Проведено аналітично-експериментальні дослідження, з огляду на які зясована можливість ефективного використання водоростевої сировини в соусах емульсійного типу. Встановлено, що використання водоростевої сировини як йодовмісних добавок виявилося бажаним, оскільки водорості містять значну кількість органічного йоду легкозасвоюваних формах. Найпоширенішими джерелами є бурі морські водорості вакаме та комбу. Тому вважається, що додавання вищезазначених водоростей навіть у не великій кількості до складу емульсійних соусів не тільки не погіршить органолептичних показників, а і задовольнить добову потребу людини в йоді, оскільки це досить важливо і актуально в умовах йоддифіциту. Проведений органолептичний аналіз емульсійних соусів, результат якого показав, що розроблені соуси мають смакові властивості, які є звичними для споживачів і позитивно впливатимуть на сприймання інноваційного продукту. Для оцінки якості соусів емульсійного типу було застосовано бальну систему оцінювання на основі та з урахуванням коефіцієнта важливості, що дозволило в значній мірі продемонструвати високу якість органолептичних показників одержаних соусів. EN: The article considers the main stages, directions and feasibility of using iodine-containing wakame and kombu additives in the production of emulsion sauces. Analytical and experimental studies were conducted, on the basis of which the possibility of effective use of algal raw materials in emulsion-type sauces was studied. It has been established that it is advisable to use algae raw materials as an iodine-containing additive, since it contains a significant amount of organic iodine in an easily digestible form. The largest amount of it is found in brown seaweed wakame and kombu. Therefore, it is assumed that the addition of even a small amount of algae, that is, one that is not reflected on the organoleptic indicators, to the composition of the emulsion sauce, will allow to satisfy the daily need of a person for iodine, which is quite relevant in conditions of iodine deficiency. An organoleptic analysis was carried out, thanks to which it was established that the developed emulsion sauces are characterized by taste properties familiar to the consumer, which will positively influence the perception of the innovative product. A scoring system for evaluating the quality of sauces has been developed, taking into account the coefficient of importance. The implementation of this system made it possible to clearly demonstrate the high organoleptic quality indicators of the sauces obtained. It was established that the introduction of algae into the sauce recipe in concentrations of 5...15%. does not deteriorate the organoleptic indicators of emulsion sauces, increases the total content of minerals and vitamins in the product, the stability of the emulsion increases due to the stabilizing effect of wakame and kombu polysaccharides. The material of article reflects the main factors of making combination products – emulsion sauce with algae. It is proved that algae belong to unique sources of macro- and micronutrients, proteins, minerals, vitamins, enzymes, phytohormones, alginic, pantothenic and folic acid, amino acids, polysaccharides. Besides, algae are unique raw material that capable of forming a large biomass in a short time. Emulsion sauces are a source of polyunsaturated fatty acids, because they contain vegetable fats, which improve its utilizatio in an emulsified state. In this elaboration, the role of algal additives is not limited to their benefits, they also have a technological effect.
Investigation of organoleptic quality indicators of emulsion sauces with iodine replacement additives
Keywords: водоростева сировина; йодовміщуючі добавки; вакаме; комбу; емульсійний соус; органолептичні показники; algae raw materials; iodine-containing additives; wakame; kombu; emulsion sauce; organoleptic indicators